Effect of 3p- and 5d-electron doping on the Kondo Semiconductor CeFe2Al10. Issue 1 (1st March 2022) - Tripathi, Rajesh; Adroja, D T; Lees, M R; Anand, V K; Sundaresan, A; Langridge, S; Bhattacharyya, A; Muro, Y; Hayashi, K; Takabatake, T
Abstract: We examined the effect of 3 p - and 5 d -electron doping on the Kondo semiconductor CeFe2 Al10 by means of the electrical resistivity ( ρ ), magnetic susceptibility ( χ ), and specific heat ( C ) measurements. The results show that in the 3 p -electron-doped system CeFe2 Al10− y Si y, the semiconducting behavior is suppressed for y = 0.05, and the system adopts a metallic ground state with an increase in the density of states at the Fermi level. The Si substitution leads to a large decrease in the paramagnetic Weiss temperature θP indicating a reduction in c-f hybridization strength, however the Si does not induce magnetic order up to y = 0.3 down to 2K. The systematic changes in ρ ( T ), χ ( T ), and C ( T ) are similar to those for 5 d -electron doped system CeFe2− x Ir x Al10, although, Ir substitution induces a bulk antiferromagnetic transition below 3.1 K in CeFe1.7 Ir0.3 Al10 . These changes can be explained by the collapse of the hybridization gap due to the suppression of the c-f hybridization effect. Our results further confirm that the collapse of the spin/charge gap by an excess electron doping is one of the universal features of the Kondo semiconductors Ce T 2 Al10 ( T = Fe, Ru, and Os).